Organelle trafficking, the cytoskeleton, and pollen tube growth. Issue 1 (11th December 2014) - Cai, Giampiero; Parrotta, Luigi; Cresti, Mauro
Abstract The pollen tube is fundamental for the reproduction of seed plants. Characteristically, it grows relatively quickly and uni‐directionally ("polarized growth") to extend the male gametophyte to reach the female gametophyte. The pollen tube forms a channel through which the sperm cells move so that they can reach their targets in the ovule. To grow quickly and directionally, the pollen tube requires an intense movement of organelles and vesicles that allows the cell's contents to be distributed to sustain the growth rate. While the various organelles distribute more or less uniformly within the pollen tube, Golgi‐released secretory vesicles accumulate massively at the pollen tube apex, that is, the growing region. This intense movement of organelles and vesicles is dependent on the dynamics of the cytoskeleton, which reorganizes differentially in response to external signals and coordinates membrane trafficking with the growth rate of pollen tubes. <inline-graphic xlink:href="ark:/27927/pgh30vxbbk5" content-type="jipb12289-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Giampiero Cai